Reactualization the Concept of Khayra Ummaá¸¥ According to Muá¸¥ammad 'Abduh and Muá¸¥ammad RashÄ«d Riá¸Ä in TafsÄ«r al-ManÄr - Rijal Ali; Akhmad Shagir (Jurnal Ushuluddin, 2023)
The limited interpretation of the Khayra Ummaá¸§ concept is one of the reasons for the backwardness of Muslims, that caused limiting its actualization and benefits. It is necessary to re-actualize the concept of khayra ummaá¸§ which comes from the thoughts of the experts in social field. Therefore, this article attempts to reveal the re-actualization of the concept of khayra ummaá¸§ according to Muá¸¥ammad 'Abduh and Muá¸¥ammad RashÄ«d Riá¸Ä. This research is a library research with descriptive-analytical method. It is preceded by describing the interpretation of Muá¸¥ammad 'Abduh and Muá¸¥ammad RashÄ«d Riá¸Ä regarding QS. Ä€li-â€˜ImrÄn [3]: 104 and 110. The findings were analyzed to reveal the re-actualization of the concept of khayra ummaá¸§ according to Muá¸¥ammad 'Abduh and Muá¸¥ammad RashÄ«d Riá¸a. After conducting several stages, the re-actualization of the concept of khayra ummaá¸§ based on Muá¸¥ammad 'Abduh and Muá¸¥ammad RashÄ«d Riá¸Ä can be summed up into three major points, namely (1) humanization; (2) work professionalism and humanization; and (3) belief in Allah as the principle of truth. A humanist personality can be realized through awareness of the existence of amar ma'ruf and nahÄ« munkar which is a requirement as khayra ummaá¸§. It makes Muslim courteous and do not acts of cruelty beyond humanity